2008
DOI: 10.1080/17470210701625550
|View full text |Cite
|
Sign up to set email alerts
|

Processing Abstract Language Modulates Motor System Activity

Abstract: Embodiment theory proposes that neural systems for perception and action are also engaged during language comprehension. Previous neuroimaging and neurophysiological studies have only been able to demonstrate modulation of action systems during comprehension of concrete language. We provide neurophysiological evidence for modulation of motor system activity during the comprehension of both concrete and abstract language. In Experiment 1, when the described direction of object transfer or information transfer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
265
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 333 publications
(291 citation statements)
references
References 38 publications
20
265
0
6
Order By: Relevance
“…In accordance with previous work [5,24] a fronto-parietal circuit related to language or better to linking meaning to symbols in a modalityindependent way may be used for comprehension of symbolic gesture and corresponding word. In contrast, motor circuits including primary motor area are likely activated to comprehend action words used in actual and even metaphoric context [8,25].…”
Section: Article In Pressmentioning
confidence: 99%
“…In accordance with previous work [5,24] a fronto-parietal circuit related to language or better to linking meaning to symbols in a modalityindependent way may be used for comprehension of symbolic gesture and corresponding word. In contrast, motor circuits including primary motor area are likely activated to comprehend action words used in actual and even metaphoric context [8,25].…”
Section: Article In Pressmentioning
confidence: 99%
“…These authors suggested that in addition to sensorimotor representations, parts of the motor system may code for abstract semantic features like changes of state. Glenberg et al (2008), using TMS, likewise observed modulation of corticospinal motor pathways to hand muscles when subjects read abstract sentences reflecting transfer of information (e.g., Arthur presents the argument to you). Given such findings, what steps can be taken to ensure that motor activation to words denoting a physical movement actually reflects a representation of the implied action?…”
mentioning
confidence: 99%
“…The most straightforward inference-that motor activation is a necessary part of word comprehension (e.g., Gallese & Lakoff, 2005;Glenberg et al, 2008)-is contentious, given traditional linguistic analyses of meaning. These analyses assume a distinction between the abstract conceptual structure of a word (coding for semantic properties like the word's predicate-argument structure and its category membership) and the sensorimotor representations of physical objects (Jackendoff, 1996(Jackendoff, , 2002.…”
mentioning
confidence: 99%
“…Embodied theories suggest that higher cognitive processes, like math and language, are ultimately based on sensorimotor codes within a generalized system that was originally developed to control an organism's motor behavior and perceive the world around it (Barsalou 1999). Evidence for this embodied cognition paradigm comes from many different research domains, ranging from research on action semantics (Lindemann et al 2006), language and reading comprehension (De Koning and Van der Schoot 2013;Zwaan and Taylor 2006), and cognitive neuroscience (Glenberg et al 2008;Martin 2007). These studies show that visual and motor processes are activated in the brain during the performance of cognitive tasks (e.g., math, reading, problem solving), while semantic codes are active when participants perform motor tasks, suggesting a close interrelationship between cognitive and sensorimotor processes.…”
mentioning
confidence: 99%